The Principle of Respect for Regional Sovereignty (Iraq as an Example) - Esraa Nader; Luma Abd-Al-baqi Mahmood (Journal of Legal Sciences, 2024)
This research aims to clarify the principle of respecting the territorial sovereignty of the state, which is considered one of the most important terms within the framework of public international law because it is one of the most important components of the state and through which the state exercises its authority over its territory internally and externally. Therefore, international law focused on the necessity of respecting the territorial sovereignty of the state and not violating it through stipulating it in international agreements and charters, the most important of which is the United Nations Charter of 1945, which emphasized the necessity of respecting the sovereignty of states by prohibiting the use of force and not allowing interference in their internal affairs in order to preserve the sovereignty of states and thus maintain international peace and security, but despite all this, we find violations by some countries, and because of the recent developments taking place and the attack on Iraq’s sovereignty, it was necessary to shed light on this issue, especially the recent attacks carried out by Turkey and Iran, in which they violated the sovereignty of the Iraqi state, including This violation violates the rules of international law and any violation of the latter entails international responsibility.